IMPLEMENTASI FSSC 22000 SEBAGAI MODAL KEUNGGULAN BERSAING PERUSAHAAN TVP DALAM BERETIKA BISNIS - Mochamad Saefullah; Yurisna Apriamy; Juwita Juwita (Jurnal Bina Bangsa Ekonomika, 2023)
Food Safety System Certification 22000 (FSSC 22000) is a standard for conducting certification that focuses on food safety. The implementation of FSSC 2200 is one of the steps used to enable companies to compete in the global arena. The implementation of FSSC 22000 cannot be separated from the role of all layers of employees in the company, all employees have a very vital role in the effort to implement FSSC 22000. FSSC 22000 as a company's competitive advantage in business ethics. This study uses a literature approach as the method used in examining phenomena related to the implementation of FSSC 22000 which is a competitive advantage for TVP companies in business ethics